Formation laws and mechanism of freezing temperature fields of multiple coil tubes under groundwater seepage conditions - Chuanxin RONG; Runze ZHANG; Wei LONG; Shiqing HUANG; Jihao FENG (Meikuang Anquan)
In order to study the formation law of artificial frozen temperature field and the formation mechanism of frozen wall in deep alluvial layer under the action of groundwater seepage, the paper analyzes the spatiotemporal evolution law of frozen temperature field under different layers and soil properties based on the construction background of central wind shaft freezing method in Linhuan Mine. The data is used to verify the rationality of the groundwater thermal coupling numerical calculation model based on the actual location of frozen hole in the field and the buried depth of 228 m sand layer. Based on this model, the influence of groundwater seepage on the formation rule and development mechanism of freezing temperature field is explored. The results show that the soil inside the ring diameter is affected by the superposition of cooling capacity, and the cooling is faster than that outside, and the freezing phase is more obvious in the freezing process of the multiple coil tubes. The temperature on the main surface of the frozen soil in the double coil tube is “saddle shape” and the temperature on the interface is “parabolic shape”, and the temperature on the main surface drops faster than that on the interface. The different seepage velocity of groundwater has a great influence on the circulation time and circulation pattern of frozen wall. The circulation time can be fitted with the “two-stage response function”, and the groundwater limit flow rate of the two stages is 21 m/d. When the seepage velocity increases from 0 m/d to 40 m/d, the thickness of the frozen wall in the upper reaches and flanks decreases by 25.06% and 16.41%, respectively, while the thickness of the frozen wall in the lower reaches increases by 59.29%. The increase of groundwater flow rate increases the asymmetric development and distribution of the temperature field of the freezing wall, and induces the asymmetric “bad development” of the freezing wall.